2015
DOI: 10.1159/000369441
|View full text |Cite
|
Sign up to set email alerts
|

The WHO Framework Convention on Tobacco Control

Abstract: Tobacco is among the major preventable causes of death in the world today. The World Health Organization (WHO) estimates that tobacco kills about 6 million people yearly. The tobacco epidemic is devastating but preventable by strong political measures. This was the reason why in 1996 the World Health Assembly requested WHO to initiate the first treaty negotiated under the auspices of WHO in history: the WHO Framework Convention on Tobacco Control (WHO FCTC). In 2005, this Convention entered into force and chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…4 Since COVID-19 has a severe stage of pneumonia or respiratory failure, smokers are much susceptible to severe disease because of their immunocompromised lungs. 7 In an article from the area of pulmonology, Brake et al explained the biological process of coronavirus attacking the human body, where they stated that smoking is one factor that accelerates the production of the angiotensin-converting enzyme-2 (ACE2) receptor, which is known to be the receptor of coronavirus, and therefore smokers are more vulnerable to this disease than non-smokers. 8,9 Reviewing seven study reports, Zhao et al concluded that although the association between smoking and COVID-19 is non-significant, active smoking increases the risk of having severe COVID-19 and smokers have 1.98 times greater risk of having the severe stage.…”
Section: Introductionmentioning
confidence: 99%
“…4 Since COVID-19 has a severe stage of pneumonia or respiratory failure, smokers are much susceptible to severe disease because of their immunocompromised lungs. 7 In an article from the area of pulmonology, Brake et al explained the biological process of coronavirus attacking the human body, where they stated that smoking is one factor that accelerates the production of the angiotensin-converting enzyme-2 (ACE2) receptor, which is known to be the receptor of coronavirus, and therefore smokers are more vulnerable to this disease than non-smokers. 8,9 Reviewing seven study reports, Zhao et al concluded that although the association between smoking and COVID-19 is non-significant, active smoking increases the risk of having severe COVID-19 and smokers have 1.98 times greater risk of having the severe stage.…”
Section: Introductionmentioning
confidence: 99%
“…prevalensi perokok tembakau di seluruh dunia mencapai 1,3 milyar, terutama di negara berkembang, termasuk Indonesia yang merupakan negara urutan terbesar ketiga setelah Cina dan India (Pötschke-Langer, Schotte, & Szilagyi, 2015). Menurut data Tobacco Control Support Centre (2015), prevalensi perokok di Indonesia berdasarkan jenis kelamin memiliki kesamaan dari tahun sebelumnya, yakni perokok laki-laki lebih tinggi daripada perempuan.…”
Section: Agamaunclassified
“…In response to the global tobacco epidemic and to reduce the related morbidity and mortality, the World Health Organization Framework Convention on Tobacco Control (WHO FCTC) 48 was put into action in 2005 49,50 after many years in the making. In fact, the need for an international strategy was voiced as early as 1979, and, 10 years later, the work was actually initiated 49 . In 1993, the notion of an international convention was proposed, although initially criticised by WHO for being overly ambitious 51 .…”
Section: International Tobacco Controlmentioning
confidence: 99%
“…Five years later and after considerable efforts and obstruction attempts by the tobacco industry, the convention was ready. It built on an alliance between the WHO, World Bank, United Nations International Children's Emergency Fund (UNICEF), researchers and other relevant partners 49,51 . Two years after opening for signatures by member states, the WHO FCTC was put into action, with 168 of the 192 member states having signed.…”
Section: International Tobacco Controlmentioning
confidence: 99%
See 1 more Smart Citation